Altered distribution and function of NK-cell subsets lead to impaired tumor surveillance in JAK2V617F myeloproliferative neoplasms - Fernandes de Oliveira Costa, Amanda; Olops Marani, Leticia; Mantello Bianco, Thiago; Queiroz Arantes, Adriana; Aparecida Lopes, Izabela; Antonio Pereira-Martins, Diego; Carvalho Palma, Leonardo; Santos Scheucher, Priscila; Lilian dos Santos Schiavinato, Josiane; Sarri Binelli, Larissa; Araújo Silva, Cleide; Kobayashi, Susumu S.; et al. (Frontiers in Immunology, 2022)
In cancer, tumor cells and their neoplastic microenvironment can sculpt the immunogenic phenotype of a developing tumor. In this context, Natural Killer (NK) cells are lymphocytes of the innate immune system recognized for their potential to eliminate neoplastic cells through direct cytolytic activity and by favoring the development of an adaptive anti-tumor immune response. Protective effect against leukemia due to NK cell alloreactivity mediated by the absence of the KIR-ligand has already been shown, but the role of NK cells in myeloproliferative neoplasms (MPN) has not been fully investigated. It is still unclear whether NK cells can affect the biology of BCR-ABL1-negative MPN and which mechanisms are involved in the control of leukemic stem cell (LSC) expansion. In order to investigate the potential contribution of NK cells to the pathogenesis of MPN, we characterized the frequency, receptor expression, maturation profile, and function of NK cells from a conditional Jak2V617F (Jak2VF) murine transgenic model, which resembles the main clinical and laboratorial characteristics of human Polycythemia Vera (PV), and from MPN patients. Immunophenotypic analysis was performed to characterize NK frequency, their subtypes, and receptor expression. We observed a higher frequency of NK cells in JAK2V617F mutated MPN and a maturation arrest that resulted in low numbered mature CD11b+ NK cells and increased immature secretory CD27+ cells in both human and murine JAK2V617F mutated samples. In agreement, inhibitory receptors were more expressed in JAK2V617F mutated MPN. NK cells from Jak2V617F mice presented a lower potential for proliferation and activation than wild-type NK cells. Colonies generated by murine Lin-, Sca-1+, cKithi, SLAM+ cells after Jak2WT or Jak2VF NK co-culture exposure demonstrated that NK cells from Jak2V617F mice are deficient in regulating the differentiation and clonogenic capacity of hematopoietic stem cells (HSC). In conclusion, our findings suggest that NK cells have an immature profile, with deficient cytotoxicity, that may lead to impaired tumor surveillance in MPN. These data provided a new perspective on the behavior of NK cells in the context of myeloid malignancies and can contribute to the development of new therapeutic strategies, targeting onco-inflammatory pathways that can potentially control transformed HSCs.